2021
DOI: 10.1021/jacs.1c01045
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Enzyme, Viperin, Activates Protein Ubiquitination by the E3 Ubiquitin Ligase, TRAF6

Abstract: Viperin is a broadly conserved radical SAM enzyme that synthesizes the antiviral nucleotide ddhCTP. In higher animals, viperin expression also accelerates the degradation of various cellular and viral proteins necessary for viral replication; however, the details of this process remain largely unknown. Here, we show that viperin activates a component of the protein ubiquitination machinery, which plays an important role in both protein degradation and immune signaling pathways. We demonstrate that viperin bind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The prevailing hypothesis is that viperin promotes ubiquitin-dependent degradation of target proteins by recruiting an (as yet undefined) E3 ubiquitin ligase to polyubiquitinate the target, thereby marking it for degradation. This hypothesis chimes with the recent observation that viperin stimulates Lys63-linked auto-ubiquitination of the E3 ubiquitin ligase, TRAF6 (Patel & Marsh, 2021).…”
supporting
confidence: 84%
“…The prevailing hypothesis is that viperin promotes ubiquitin-dependent degradation of target proteins by recruiting an (as yet undefined) E3 ubiquitin ligase to polyubiquitinate the target, thereby marking it for degradation. This hypothesis chimes with the recent observation that viperin stimulates Lys63-linked auto-ubiquitination of the E3 ubiquitin ligase, TRAF6 (Patel & Marsh, 2021).…”
supporting
confidence: 84%
“…In support of this idea, the ubiquitin-dependent degradation of SM is known to be regulated in response to cellular cholesterol levels through the action of the E3 ubiquitin ligase, Membrane Associated Ring-CH-Type Finger 6 ( 11 ), and it is generally considered that viperin exerts some of its antiviral effects by increasing the rate of proteasomal degradation of its target proteins ( 15 , 68 ). Although the evidence for viperin's interaction with proteasomal degradation machinery is indirect, viperin has recently been shown to activate TRAF6 ( 72 ), which is an E3 ligase involved in the K63-linked polyubiquitination of proteins involved in immune signaling ( 49 , 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were resuspended in lysis buffer (TBS, 0.1% Tween-20, and Complete Protease Inhibitor Cocktail) and lysed as described previously. All assays were performed in lightproof tubes and performed as previously described ( 72 ), but with minor modifications. Briefly, assays contained 200 μl cleared HEK cell lysate prepared from cells expressing the protein(s) of interest, 0.1 mM flavin adenine dinucleotide, and 1 mM NADPH.…”
Section: Methodsmentioning
confidence: 99%
“… 225 Additional studies suggested that viperin exerts its antiviral effect by activating a component of the protein ubiquitination machinery with subsequent degradation of cellular and viral proteins essential for viral replication. 226 …”
Section: Rabies Virus (Rabv)mentioning
confidence: 99%